STUDI MENGENAI KEPUASAN PELANGGAN DALAM MENGGUNAKAN JASA PERBANKAN DI SURAKARTA - Triastity, Rahayu - (Universitas Slamet Riyadi, 2009)
ABSTRACT Target of this research is (1) to know significant influence product, service, facility, security, and location to costumer satisfaction Banking Service. (2) to know factor which having an effect on dominant to costumer satisfaction Banking Service. This research type is quantitative, that is in research which aim to obtain get verification from a hypothesis, by using predicted parameter test (test t). to test question instrument used by validity test and reliability test, while classic assumption test which used by is heteroskedastisity, autocorrelation, and multicolinerity. Result of research show: (1) Examination of hypothesis by partial (test t) shall be as follows: (a) Product variable have an effect significant to consumer satisfaction proved by level of t-statistic value = 2,495 with probability value = 0,015 < 0,05. (b) Service variable have an effect significant of t-statistic value = 2,369 with probability value = 0,021 < 0,05. (c) Facility variable have an effect significant to consumer satisfaction proved by level of t-statistic value = 2,762 with probability value = 0,007 < 0,05. (d) Security variable haven't an effect significant to consumer satisfaction proved by level of t-statistic value = 0,911 with probability value = 0,366 > 0,05. (e) Location variable have an effect significant to consumer satisfaction proved by level of t-statistic = 2,044 with probability value = 0,045 < 0,05. (2) Examination of hypothesis accuracy of model (test F) show F value calculated equal to = 42,632 with level of significant 0,000. Probability value 0,000 < 0,05 matter give meaning that examination of used by model that is product factor, service, facility, security, and location proven by at a time have an effect significant to consumer satisfaction. (3) Service factor have strongest contribution in influencing consumer satisfaction. This matter because of level of regression coefficient value equal to = 0,287 is which the biggest to be compared with fourth of other variable. Keywords: product, service, facility, security, location, and consumer satisfaction.